Peran Sistem Informasi Manajemen Rumah Sakit Terhadap Kecepatan Layanan IGD Di Rumah Sakit Mitra Manakarra Mamuju - Ramadhani, Putri Nur; Resti, Andhiny Mantasya; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study aims to analyze the role of the Hospital Management Information System (SIMRS) in improving the speed of Emergency Department (ED) services at Mitra Manakarra Mamuju Hospital. The research employed an empirical approach using a descriptive qualitative method through observations of service flow and informal interviews with ED medical staff. Although no formal quantitative data were used, the study constructed realistic scenarios of service duration before and after SIMRS implementation. The findings indicate that SIMRS accelerates patient registration, triage, access to medical records, and information integration across service units, resulting in a significant reduction in patient waiting time. The discussion confirms that these findings align with previous studies asserting that hospital digitalization plays a crucial role in enhancing clinical responsiveness. The study concludes that SIMRS greatly contributes to the efficiency of ED services and recommends improving medical staff competence and digital infrastructure to support sustainable SIMRS implementation.